Benthic foraminiferal census counts from sediment core MD03-2611 (South Australian margin, AUSCAN cruise) - Robin Fentimen; Pauline Depuydt; Meryem Mojtahid (PANGAEA, 2023)
The data presents benthic foraminiferal census counts from gravity core MD03-2611. The 11.97 m long core MD03-2611 was collected during the AUSCAN cruise in 2003 on-board the research vessel Marion Dufresne II (Hill and De Deckker, 2004). It was retrieved from a small plateau south of Kangaroo Island at 2420 m depth (36°43.80 extquotesingleS, 136°32.90 extquotesingleE) facing the mouth of the Murray River. The datasets cover the last 94 ka and have been used to understand how deep-sea benthic environments respond to changes occurring within surface waters and on land.